2010
DOI: 10.1016/j.sbi.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

SF1 and SF2 helicases: family matters

Abstract: Helicases of the superfamily (SF) 1 and 2 are involved in virtually all aspects of RNA and DNA metabolism. SF1 and SF2 helicases share a catalytic core with high structural similarity, but different enzymes even within each superfamily perform a wide spectrum of distinct functions on diverse substrates. To rationalize similarities and differences between these helicases, we outline a classification based on protein families that are characterized by typical sequence, structural and mechanistic features. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
945
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 815 publications
(1,001 citation statements)
references
References 99 publications
19
945
1
Order By: Relevance
“…A number of structural studies have universally shown that members of the DEAD box family contain a highly conserved helicase core that harbours the binding sites for ATP and RNA 3,4,8 . The core is surrounded by variable auxiliary domains, which are thought to be critical for the diverse functions of these enzymes.…”
Section: Structures Of Dead Box Rna Helicasesmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of structural studies have universally shown that members of the DEAD box family contain a highly conserved helicase core that harbours the binding sites for ATP and RNA 3,4,8 . The core is surrounded by variable auxiliary domains, which are thought to be critical for the diverse functions of these enzymes.…”
Section: Structures Of Dead Box Rna Helicasesmentioning
confidence: 99%
“…DEAD box proteins belong to helicase superfamily 2 (SF2) 2 . Similarly to all SF2 helicases, DEAD box proteins are built around a highly conserved helicase core of two virtually identical domains that resemble the bacterial recombination protein recombinase A (RecA) 3,4,8 (FIG. 2a,b).…”
Section: Structures Of Dead Box Rna Helicasesmentioning
confidence: 99%
See 3 more Smart Citations